Impact of Water Conservation Schemes on Narnaund Block’s Food Security - Pardeep Kumar*, Rajesh Malik, Kulvinder Kaur** (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Water conservation is a crucial aspect of sustainable agriculture, particularly in semi-arid regions like the Narnaund block of Hisar, Haryana. Water being a state subject, sustainable development and management of groundwater resources is primarily the responsibility of the State Governments. This research paper examines the impact of various water conservation schemes on food security in the region. Government initiatives such as the Pradhan Mantri Krishi Sinchayee Yojana (PMKSY), Mera Pani Meri Virasat, and micro-irrigation programs have significantly enhanced water-use efficiency, leading to increased agricultural productivity. The study evaluates the effectiveness of these interventions in mitigating groundwater depletion, ensuring stable crop yields, and enhancing farmers’ livelihoods. Findings indicate that improved irrigation techniques, rainwater harvesting structures, and policy-driven incentives have contributed to better water management and food security. However, challenges such as over-extraction of groundwater and irregular monsoon patterns remain persistent. The research suggests that integrating modern irrigation technologies with farmer awareness programs can further strengthen water conservation efforts and ensure long-term agricultural sustainability in Narnaund block. This study provides insights into policy recommendations for enhancing water resource management and securing food production in water-stressed regions.